Mindfulness Training Intervention With the Persian Version of the Mindfulness Training Mobile App for Premenstrual Syndrome: A Randomized Controlled Trial - Mazaheri Asadi, Dorsa; Zahedi Tajrishi, Komeil; Gharaei, Banafsheh (Frontiers in Psychiatry, 2022)
Premenstrual syndrome (PMS) is a common problem for women of reproductive age, affecting various aspects of their lives. While various in-person psychotherapeutic interventions, including Mindfulness therapy, have yielded promising results in reducing PMS symptoms, due to the COVID-19 Pandemic, psychotherapists are providing their services via online methods. Therefore, the present study is the first one worldwide to examine whether smartphone-based Mindfulness training can reduce symptoms of PMS and improve the quality of life in women with PMS. We recruited 80 Iranian women (aged 25 to 45) with PMS through online advertising who were randomly allocated into two groups of 40. The intervention group underwent two online introductory group sessions followed by eight weeks of Mindfulness practice, while the control group received no intervention. Before and after the intervention, participants completed the 12-Item Short-Form Health Survey and the Premenstrual Symptoms Screening (PSST) questionnaires. Data were analyzed using the Analysis of Covariance (ANCOVA). Following the intervention, the mean scores of PMS symptoms were significantly lower in the intervention group than in the control group (p < 0.001; η2 = .18). Likewise, the quality of life score was significantly higher in the intervention group (p < 0.001; η2 = .14). Our results indicated that the smartphone-based Mindfulness training intervention could be an effective treatment modality for women with PMS symptoms, especially during the COVID-19 Pandemic, which has posed limitations for in-person therapies.